02 TANGGAPAN KONSUMEN TERHADAP JAGUNG PULUT REBUS DI KECAMATAN SIMBANG, KABUPATEN MAROS - Jurnal Agribis; Kahar Maulana; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2021)
Pulp corn is one type of corn with a pulut taste or sticky rice, so it is rather sticky and fluffier when boiled. This research was conducted in Simbang District, Maros Regency. This location was chosen with consideration of accedetial sampling. The data used are primary data obtained from observations through direct interviews and also through the help of questionnaire lists. The purpose of this study was to determine consumer responses to boiled pulut corn in Simbang District, Maros Regency, and to find out the most influential and dominant factors affecting boiled corn. Data was collected from the survey results using a questionnaire and added with observations / field observations. The collected data is then tabulated to obtain the real data used for analysis purposes. This research uses quantitative descriptive analysis method to determine consumer responses to boiled pulut corn, and the method of multiple regression analysis to determine the influential and most dominant factors affecting pulut boiled corn. The results of this study can be seen that the responses of consumers of Simbang District's boiled corn are included in the high category with price and taste indicators. The factors that significantly influence consumers' responses to boiled corn are price and taste.